Calculated Lattice Thermal Conductivity of Magnetite Thin Films based on Modified Callaway Model - Qader, Ibrahim Nazem; Oner, Ecem; Kok, Mediha (Gazi Univ, 2022)
Thermal conductivity is an important parameter for semiconductor materials used in the nanoscale applications. In this study, the lattice thermal conductivity (LTC) of magnetite thin films was simulated by Modified Callaway Model. To fit the experimental data, some quantities, such as mean bond length, the lattice constant, and volume per atom were calculated. Also, the model is based on some other quantities, such as gruneisen parameter, electron concentration, and surface roughness that were found through fitting theoretical with experimental LTC. As a result, this model could work comparably well in all sizes, and the relationship between the fitting parameters and the thickness of the magnetite films was estimated.
Keywords: Magnetite; Fe3O4; Thin film; Lattice thermal conductivity; Modified Callaway Model